FARMERS’ PERCEPTIONS OF THE GOVERNMENT POLICY REGARDING FOOT AND MOUTH DISEASE (FMD) VACCINATION FOR SLAUGHTER CATTLE IN TIKUNG DISTRICT, LAMONGAN REGENCY - D. W, ASPRIATI; ., SUMARTONO; MUWAKHID, B. (Majalah Ilmiah Peternakan; Vol 27 No 3 (2024): Vol. 27 No. 3 (2024)DO - 10.24843/MIP.V27.i03.p03, 2024)
Foot-and-Mouth Disease (FMD), caused by the Foot-and-Mouth Disease Virus (FMDV), is a highly contagious acute infection affecting cloven-hoofed animals. In Lamongan Regency, outbreaks of PMK in cattle have led to a decline in population. Despite vaccination programs, farmers’ willingness to vaccinate is influenced by perceptions of vaccine safety and effectiveness. Increasing vaccination coverage is hoped to restore PMK-free status in the area. This research aims to understand the influence of farmers’ perceptions on government policies regarding PMK vaccination in cattle in Tikung District, Lamongan Regency, and to identify factors affecting these perceptions. The study employs a mixed-methods approach with a sequential explakomuninatory design. Data collection instrumen ts include questionnaires and interview guidelines, utilizing both survey distribution and in-depth interviews with informants. Quantitative data analysis involves univariate and bivariate analyses, while qualitative analysis uses an interactive model. Research findings indicate a significant positive influence of farmers’ perceptions on PMK vaccination policies in Tikung District, Lamongan Regency (significance value of 0.000 (0.000 < 0.05) and t value of 5.894 > t table (1.9858)). Factors such as extensive knowledge of PMK and vaccination programs, personal expe- rience with the disease, and support from the government and livestock groups contribute to positive perceptions of these policies. However, challenges such as concerns about post-vaccination side effects and timing conflicts with farmers’ village activities affect participation rates and trust in the program.